The Gospel as Literary Genre and Form of Language - Pasquale Basta (The Biblical Annals, 2021)
The studies on the literary genre “gospel” are often compared with the so-called Greco-Roman bíoi and popular literature. The points of contact are numerous and undeniable. As well as the differences and peculiarities of the gospels, whose link with the Hebrew Bible is a unicum to be taken into account. In particular, the typology, with its network of references, makes the canonical gospels a text proceeding through continuous phenomena of association and repetition with the ancient Scriptures. As result, the narrative takes on particular tones insofar as it indulges little in the chronicle, concentrating rather on the richness of meaning hidden in entire story of Christ. Consequently, the gospels are evidence of a mixed genre, having some characteristics of the Greco-Roman bíoi and contemporary popular Lives, together with constant re-elaboration of OT elements re-read and applied in a typological key. And it could not be otherwise because the events and the protagonist of the gospels perfectly intersect the horizontal and vertical dimensions of a story merging with the eternal.